Impact of implementing evidence-based acute stroke interventions on survival: the South London Stroke Register. - Juliet Addo; Siobhan Crichton; Ajay Bhalla; Anthony G Rudd; Charles D A Wolfe; Christopher McKevitt (PLoS ONE)
Background Studies examining the impact of organised acute stroke care interventions on survival in subgroups of stroke patients remain limited. Aims This study examined the effects of a range of evidence-based interventions of acute stroke care on one year survival post-stroke and determined the size of the effect across different socio-demographic and clinical subgroups of patients. Methods Data on 4026 patients with a first-ever stroke recruited to the population-based South London Stroke Register between 1995 and 2010 were used. In uni-variable analyses, one year cumulative survival rates in socio-demographic groups and by care received was determined. Survival functions were compared using Log-rank tests. Multivariable Cox models were used to test for interactions between components of care and age group, sex, ethnic group, social class, stroke subtype and level of consciousness. Results 1949 (56.4%) patients were admitted to a stroke unit. Patients managed on a stroke unit, those with deficits receiving specific rehabilitation therapies and those with ischaemic stroke subtype receiving aspirin in the acute phase had better one year survival compared to those who did not receive these interventions. The greatest reduction in the hazards of death among patients treated on a stroke unit were in the youngest patients aged <65 years, (HR 0.39; 95% CI: 0.25-0.62), and those with reduced levels of consciousness, GCS <9, (HR: 0.44; CI: 0.33-0.58). Conclusions There was evidence of better one year survival in patients receiving specific acute interventions after stroke with a significantly greater effect in stroke subgroups, suggesting the possibility of re-organising stroke services to ensure that the most appropriate care is made accessible to patients likely to derive the most benefits from such interventions.